Attrition from HIV care among youth initiating ART in youth‐only clinics compared with general primary healthcare clinics in Khayelitsha, South Africa: a matched propensity score analysis. Issue 1 (25th January 2022) - Cassidy, Tali; Cornell, Morna; Runeyi, Pumeza; Dutyulwa, Thembie; Kilani, Charllen; Duran, Laura Trivino; Zokufa, Nompumelelo; de Azevedo, Virginia; Boulle, Andrew; Horsburgh, C. Robert; Fox, Matthew P.
Abstract: Introduction: Youth living with HIV (YLWH) are less likely to initiate antiretroviral therapy (ART) and remain in care than older adults. It is important to identify effective strategies to address the needs of this growing population and prevent attrition from HIV care. Since 2008, two clinics have offered youth‐targeted services exclusively to youth aged 12–25 in Khayelitsha, a high HIV‐prevalence, low‐income area in South Africa. We compared ART attrition among youth in these two clinics to youth in regular clinics in the same area. Methods: We conducted a propensity score matched cohort study of individuals aged 12–25 years initiating ART at eight primary care clinics in Khayelitsha between 1 January 2008 and 1 April 2018. We compared attrition, defined as death or loss to follow‐up, between those attending two youth clinics and those attending general primary healthcare clinics, using Cox proportional hazards regression. Follow‐up time began at ART initiation and ended at attrition, clinic transfer or dataset closure. We conducted sub‐analyses of patients attending adherence clubs. Results: The distribution of age, sex and CD4 count at ART initiation was similar across Youth Clinic A ( N = 1383), Youth Clinic B ( N = 1299) and general clinics ( N = 3056). Youth at youth clinics were more likely than those at general clinics to have initiated ART before August 2011 (Youth Clinic A: 16%, Youth Clinic B: 23% and general clinics: 11%). Youth clinics were protective against attrition: HR 0.81 (95% CI: 0.71–0.92) for Youth Clinic A and 0.85 (0.74–0.98) for Youth Clinic B, compared to general clinics. Youth Clinic A club patients had lower attrition after joining an adherence club than general clinic patients in adherence clubs (crude HR: 0.56, 95% CI: 0.32–0.96; adjusted HR: 0.48, 95% CI: 0.28–0.85), while Youth Clinic B showed no effect (crude HR: 0.83, 95% CI: 0.48–1.45; adjusted HR: 1.07, 95% CI: 0.60–1.90). Conclusions: YLWH were more likely to be retained in ART care in two different youth‐targeted clinics compared to general clinics in the same area. Our findings suggest that multiple approaches to making clinics more youth‐friendly can contribute to improving retention in this important group.